Expression of Functional Molecule on Plasmacytoid Dendritic Cells Is Associated With HBsAg Loss in HBeAg-Positive Patients During PEG-IFN α-2a Treatment - Cao, Weihua; Xie, Si; Zhang, Lu; Bi, Xiaoyue; Lin, Yanjie; Yang, Liu; Lu, Yao; Liu, Ruyu; Chang, Min; Wu, Shuling; Shen, Ge; Dong, Jianping; et al. (Frontiers in Immunology, 2022)
Objective: The ideal endpoint of antiviral therapy in chronic hepatitis B (CHB) patients is to clear hepatitis B surface antigen (HBsAg). This study aimed to evaluate whether the expression of functional molecules on plasmacytoid dendritic cells (pDCs) is associated with HBsAg loss in HBeAg-positive patients during peginterferon alpha-2a (PEG IFN α-2a) therapy. Methods: A single-center prospective cohort study was performed in HBeAg-positive CHB patients who were treated with PEG-IFN α-2a and followed up for 4 years. HBsAg clearance, HBeAg loss and undetectable HBV DNA achieved by PEG-IFN α-2a therapy was considered as functional cure. The frequencies of pDC and CD86+ pDC in peripheral blood, and the mean fluorescence intensity of CD86 (CD86MFI) on the surface of pDC were measured at starting therapy, after 12 and 24 weeks of therapy. Results: Of 63 patients enrolled, 17 patients achieved HBsAg loss. The baseline HBV DNA load in Non-functional-cure group was significantly higher than that in Functional cure group, and the CD86+ pDC% was significantly lower in patients without functional cure. HBV DNA load (OR=0.146, P = 0.002) and CD86+ pDC% (OR=1.183, P = 0.025) were independent factors associated with functional cure confirmed by binary logistic regression analysis. In the Functional cure group, HBsAg, HBeAg, and HBV DNA loads decreased remarkably after 12 weeks and 24 weeks of treatment compared to baseline. In Non-functional-cure group, CD86+ pDC% and CD86MFI increased significantly from baseline after 12 weeks of treatment. In the Functional cure group, compared with baseline, pDC% increased significantly at 24 weeks, while CD86MFI increased significantly after 24 weeks of treatment. Conclusion: The lower the baseline HBV DNA load and the more the baseline CD86+ pDC%, the easier it is for patients to obtain functional cure.